1997
DOI: 10.1007/s004490050403
|View full text |Cite
|
Sign up to set email alerts
|

Continuous production of citric acid with recirculation of the fermentation broth after product recovery

Abstract: A four stage process for the continuous citric acid production with recirculation of the fermentation broth has been created. The process consists of the fermentation stage, extraction stage, reextraction stage and the product stage. In the present paper only the results of the fermentation stage are presented. The fermentations have been carried out in a reciprocating-jet-bioreactor with the fungi Aspergillus niger. The in¯uence of the nitrogen concentration in the in¯uent, the age of the fungi and a strong d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Kristiansen and Sinclair, 1979 reported about a continuous single-stage citric acid fermentation under nitrogen limitation using A. foetidus, reaching citric acid concentrations up to 40 g/l at dilution rates between 0.04 and 0.21 h -1 (4.76-25 hrs RT) and a maximum productivity of 0.43 g/(l x hr) at a dilution rate of 0.075 h -1 (13.3 hrs RT). Wieczorek and Brauer, 1998 reported about a four stage process for the continuous citric acid production using A. niger, recirculating fermentation broth, that includes the fermentation, extraction, reextraction and the product stage. A considerable increase in productivity in a continuous single-stage process using A. niger, compared with the batch process, has also been reported by Kristiansen and Charley, 1981, however only 26.5 g/l of citric acid were produced at a RT of 13 hrs and pH 1.7.…”
Section: Discussionmentioning
confidence: 99%
“…Kristiansen and Sinclair, 1979 reported about a continuous single-stage citric acid fermentation under nitrogen limitation using A. foetidus, reaching citric acid concentrations up to 40 g/l at dilution rates between 0.04 and 0.21 h -1 (4.76-25 hrs RT) and a maximum productivity of 0.43 g/(l x hr) at a dilution rate of 0.075 h -1 (13.3 hrs RT). Wieczorek and Brauer, 1998 reported about a four stage process for the continuous citric acid production using A. niger, recirculating fermentation broth, that includes the fermentation, extraction, reextraction and the product stage. A considerable increase in productivity in a continuous single-stage process using A. niger, compared with the batch process, has also been reported by Kristiansen and Charley, 1981, however only 26.5 g/l of citric acid were produced at a RT of 13 hrs and pH 1.7.…”
Section: Discussionmentioning
confidence: 99%
“…Tisnadjaja et al (1996) reported about a higher productivity of citric acid using C. guilliermondii in continuous culture compared with the batch process. About a four stage process for continuous production of citric acid using A. niger has been reported by Wieczorek and Brauer (1998).…”
Section: Discussionmentioning
confidence: 99%
“…A multi-tank system was suggested for the continuous operation using A. niger, which would separate growth phase and idiophase from each other. This would essentially require higher investments and efforts, making a commercial production uneconomical (Lockwood, 1979;Milson, 1987;Crueger and Crueger, 1989;Klasson et al 1989;Saha and Takahashi, 1997;Wieczorek and Brauer, 1997;Wieczorek and Brauer, 1998). Continuous single-stage operations using A. niger yielded low citric acid concentrations (Kristiansen and Sinclair, 1979;Saha and Takahashi, 1997;Wieczorek and Brauer, 1997;Wieczorek and Brauer, 1998).…”
mentioning
confidence: 99%
“…The main actual problems at citric acid industry today are the still low productivities of discontinuous A. niger processes, requiring long operational times, higher investments and production costs, compared with the novel yeast processes (Legisa and Gradisnik-Grapulin, 1995;Anastassiadis et al 2001;Kumar et al 2003;Ikram-ul et al 2004;Ali and Ikramul, 2005;Anastassiadis and Rehm, 2005). Wieczorek and Brauer (1997) reported about slowing down of continuous citric acid formation by A. niger in a reciprocating-jetbioreactor at increasing fermentation time (more than 20 days), still without achieving of steady state conditions. Continuous operations for the production of citric acid by yeasts have increasingly received research interest in last years.…”
mentioning
confidence: 99%
See 1 more Smart Citation